Role of a New Walk Test in Pulmonary Arterial Hypertension: A Retrospective Cohort Study - Junhao Jin; Yao Mi; Aqian Wang; Bo Li; Kaiyu Jiang; Hai Zhu; Ting Liang; Hongling Su; Yunshan Cao (Pulmonary Circulation, 2025)
ABSTRACT The 6‐min walk test (6MWT) has significant prognostic value, but requires long walking distances and lacks evaluation of exercise speed. This study aimed to investigate the clinical utility of a new walk test, the 18‐meter walk test (18MWT), in patients with pulmonary arterial hypertension (PAH) as a complement to the 6MWT. In summary, a total of 117 patients with PAH from January 2018 to December 2022 were included. Spearman correlation, Cox regression, and Kaplan–Meier analysis were utilized to demonstrate the value of 18MWT in predicting disease severity and clinical worsening. The median time to complete the 18MWT was 12.8 s (interquartile range: 11.3–14.6 s). 18MWT completion time showed significant correlations with indicators such as N‐terminal pro‐brain natriuretic peptide and 6MWT distance. Adjusted Cox regression showed 18MWT time remained an independent predictor of clinical worsening (hazard ratio = 1.10; 95% confidence interval: 1.01–1.21; p = 0.026). A simplified risk stratification using WHO functional class, 6MWT distance, 18MWT time and NT‐proBNP was predictive of 1‐year clinical outcome. These results suggest that the 18MWT provides clinicians with an efficient measure that can be used to evaluate the disease severity of PAH patients and to identify those patients at greater risk for future clinical worsening as a complement to the 6MWT.